Evaluation of the force field rotor in highly skilled martial artists when moving using the shuttle method - Levitskiy A.G.; Krutoy A.N.; Matveev D.A.; Berekenov A.Zh. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to identify the characteristics of the rotational force field in which the center of mass of athletes shifts during shuttle-like movements. Methods and structure of the study. It is assumed that the athlete’s center of gravity moves in a force field , created by the athlete and gravity. For the study, the shuttle method of movement was used. The demonstration of movement was carried out by two athletes qualified as a master of sports in jiu-jitsu. Results and conclusions. The rotor of the force field, which is the athlete’s center of gravity during the shuttle movement, is not fixed in time. For different athletes, the rotor’s change from the coordinate can be either identical or opposite. Consequently, we can discuss a range of biomechanical parameters and characteristics that correspond to the correct technique, and we can also talk about various versions of the correct technique for executing the movement. A technical error refers to an action that prevents the subsequent motor task from being completed or involves an unnecessary expenditure of energy.